Comparison of Introductory Pharmacy Practice Experiences Among US Pharmacy Programs - Galinski, Christine N. (Am J Pharm Educ, 2014)
Objective. To identify the various IPPE designs utilized by US pharmacy programs. Methods. A 20-question survey was developed and distributed to experiential affairs professionals at 129 pharmacy institutions nationwide addressing school demographics and IPPE design. Results were analyzed in aggregate. Results. Ninety-three schools responded (72%). Eighty-nine percent of those reported beginning IPPE experiences in the first professional year, although there was a great variation regarding whether the IPPE was held while didactic classes were in session or during school breaks. The number of required practice experiences varied. Institutions prohibited students from completing rotations in the same pharmacy chain (72%) or hospital (70%) where employed, and from completing 2 rotations at the same site (62%). Fifty-seven percent utilized faculty members as preceptors. 51% allowed a maximum of 2 students per preceptor per practice experience. Conclusion. While clear trends existed in IPPE curricula, institutions incorporated aspects that addressed unique needs. Further research can determine the benefits and drawbacks of different IPPE designs.